2020
DOI: 10.1155/2020/4270826
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Coil Treatment on Anxiety and Depression in Emphysema

Abstract: Chronic obstructive pulmonary disease (COPD) is a widespread, preventable, and treatable disease. Emphysema is one of the primary components of COPD and manifests itself via decrease in elastic recoil, hyperinflation, and increase in air trapping. Various lung-volume-reduction treatments have come up in recent years for late-stage emphysema patients. Mental disorders and especially anxiety and depression are among the frequently encountered comorbid cases observed in COPD. The aim of our study was to examine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…5 The benefit of ECT was also reported in two retrospective trials that showed an improvement in arterial blood gas and a decrease in anxiety and depression symptoms. 6,7 To improve clinical outcomes, a post hoc analyses of the RENEW trial was conducted to identify baseline predictors of procedure success. The analysis showed that significant hyperinflation and quantitative CT scan analysis are important for patient selection.…”
Section: Introductionmentioning
confidence: 99%
“…5 The benefit of ECT was also reported in two retrospective trials that showed an improvement in arterial blood gas and a decrease in anxiety and depression symptoms. 6,7 To improve clinical outcomes, a post hoc analyses of the RENEW trial was conducted to identify baseline predictors of procedure success. The analysis showed that significant hyperinflation and quantitative CT scan analysis are important for patient selection.…”
Section: Introductionmentioning
confidence: 99%